Pemberdayaan Masyarakat Lingkar Tambang Rencana dalam Pengelolaan Lingkungan Berkelanjutan (Pengelolaan Sampah Mandiri) di Kec. Lasolo Kepulauan - Putra Sakti; Villa Eva Delvia GS (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Waste management is currently suboptimal, even though it can be processed into products with economic value. Limited knowledge and skills are obstacles to waste management. Therefore, efforts are needed to improve human resources in organic and inorganic waste management. Empowering communities around the mine to independently process waste is a top priority to create a healthy environment, create jobs, and create superior eco-friendly village products in the mining area of the Lasolo Islands sub-district. The methodological approach used is interviews and field observation.